2021
DOI: 10.1007/s40843-020-1599-2
|View full text |Cite
|
Sign up to set email alerts
|

Portable wastewater treatment system based on synergistic photocatalytic and persulphate degradation under visible light

Abstract: Highly efficient, low-cost, and portable wastewater treatment and purification solutions are urgently needed for aqueous pollution removal, especially at remote sites. Synergistic photocatalytic (PC) and persulphate (PS) degradation under visible light offers an exceptional alternative for this purpose. In this work, we coupled a TiO 2-based PC system with a PS oxidation system into a portable advanced oxidation device for rapid and deep degradation of organic contaminants in wastewater. Using hydrogenation, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…8c indicated that the current of the BP/Au/CN composite was higher than that of pure CN and BP/CN in the dark condition, indicating that BP/ Au/CN had the highest charge separation rate. The timeresolved PL decay curves were measured to further investigate the charge transfer dynamics, and the corresponding average lifetimes were calculated according to Equation (2) [46][47][48]:…”
Section: Articlesmentioning
confidence: 99%
“…8c indicated that the current of the BP/Au/CN composite was higher than that of pure CN and BP/CN in the dark condition, indicating that BP/ Au/CN had the highest charge separation rate. The timeresolved PL decay curves were measured to further investigate the charge transfer dynamics, and the corresponding average lifetimes were calculated according to Equation (2) [46][47][48]:…”
Section: Articlesmentioning
confidence: 99%
“…SO 4 − • has the capability to convert OH − to •OH and 1 O 2 (Equations ( 18) and ( 19)) [12,13]. In aqueous solutions, ozone reacts with various components in two ways: through the direct oxidation of molecular ozone, which involves a selective reaction; or an indirect mechanism by which •OH radicals are produced through ozonolysis (Equation (20)), which are non-selective and highly reactive [14]. Ozone and •OH free radicals are powerful chemical oxidants involved in the disinfection and oxidation of pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, activation is required to break the -o-o-bond and produce SO 4 − •. In the presence of light, the persulfate system uses energy from ultraviolet or visible light to break the peroxygen bond in the persulfate ion, resulting in the creation of sulfate radicals (Equations ( 1)-( 3), (28), and ( 29)) [20]. The same principle applies to the thermal activation of PS (Equations ( 30)-( 32)) [21].…”
Section: Introductionmentioning
confidence: 99%